Production and characterization of laccase for enzymatic bleaching of sago starch from potential indigenous fungi - Herman Hadafi, Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2010)
The potential use of extracellular laccase enzyme from fungal isolate on bleaching of sago starch was accessed. A total of 200 fungi isolates obtained from several different locations including sago processing mills and sago plantations were screened for laccase activities. The potential fungi Crinipellis roreri, a laccase enzyme producer was isolated from decayed sago pith obtained from Nitsei Sago Industries Sdn. Bhd., Mukah, Sarawak. The fungus was identified by Food Science Australia, a joint venture company between CSIRO and AFISC. Production of laccase was studied using shake-flask cUltur:) Highest laccase activity of crude enzyme exhibited by C. roreri was 519.5 U/mL when grown in Bhat and Wood medium with] % (w/v) soluble starch as carbon source and 1 % (w/v) com steep liquor as nitrogen source, incubated with 30 °C, pH 7.0 and agitated at 150 rpm. An incubation period of 120 hours gave optimum 'laccase activity. Fractionation of laccase activity was achieved with ammonium sulphate precipitation. Recovery of 30.7 and 59.4 % of laccase activity with purification factors of 6 and 10 were achieved with 20-40 and 40-60 % saturation, respectively. Further gel filtration chromatography of the dialyzed pooled enzyme fraction of20-6O % led to purification of laccase with specific activity of 3847.4 U/mg and molecular weight of 80 kDa. Optimum temperature and pH for purified laccase were pH 6.0 and 50 °C, respectively. The purified laccase obtained from C. roreri had the ability to bleach sago starch. An increased in the 'L' value of 8 units from 83 to 91 lightness index was achieved when 5 % (v/w) laccase with the activity of 519.5 U/mL was treated with sago starch for 3 hOUTS. The laccase enzyme from C. roreri also gave higher bleaching ability compared to commerciallaccase namely Pulpzyme® and Novozyme®. The increased in the 'L' value indicates the potential use of the laccase from C. rarer; for upgrading the Industrial Grade Starch (MS 468, 1976) ('L' value < 90) to Food Grade Starch (MS 470, 1992) ('L' i value> 90) according to the Malaysian Standard, by biological means.